Pemeriksaan Histopatologi dan Imunofluoresen pada Pemfigus Vulgaris - Devitasari, Rizky; Yuniaswan, Anggun; Retnani, Diah (Jurnal Klinik dan Riset Kesehatan, 2021)
Pemphigus vulgaris (PV) is an autoimmune disease characterized by blisters on the skin and mucous membranes. The primary lesion of PV are loose blisters, which can occur anywhere on the surface of the skin and mucosal surface. Diagnostic test aims to confirm the diagnosis of PV to other vesiculobullous disease, including skin or mucosal biopsies for histopathological examination and immunofluorescence (IF). Histopathological features intraepithelial blisters and suprabasilar achantolysis with characteristic row of tombstones which were the result of IgG autoantibodies to glycoprotein desmoglein 3 (dsg3) and partly to desmoglein 1 (dsg1). Direct immunofluorescence examination showed deposits of IgG, IgM and C3 in the intercellular spaces in the epithelium. Blood tests with the ELISA test can only be used to check the levels of autoantibodies to Dsg3 and Dsg1.